Efektivitas penggunaan alat pelindung diri (APD) pada petugas pemadam kebakaran: A literature review - Azmi, Zahnia Nurul (Holistik Jurnal Kesehatan, 2025)
Background: Occupational Safety and Health (OSH) is a critical aspect of high-risk professions such as firefighting. Firefighters face significant risks due to exposure to physical, chemical, and psychological hazards in the line of duty. The use of Personal Protective Equipment (PPE) is a fundamental component in preventing injuries and work-related illnesses. Purpose: To analyze the effectiveness of Personal Protective Equipment (PPE) usage among firefighters. Method: This study uses a literature review approach, with data sources obtained from various journals published in the last five years (2020-2025). The literature identification process was conducted through various scientific platforms such as Google Scholar, ResearchGate, ScienceDirect, and other academic search engines that provide access to relevant journals, research articles, and scientific publications. Results: Overall, various research findings emphasize that the effectiveness of PPE usage among firefighters is not solely determined by equipment availability. Other contributing factors include training, equipment condition, individual awareness, availability, and institutional supervision. Conclusion: The effectiveness of the use of personal protective equipment (PPE) by firefighters is greatly influenced by various interrelated factors.   Keywords: Firefighters; Occupational Safety and Health; Personal Protective Equipment (PPE).   Pendahuluan: Keselamatan dan Kesehatan Kerja (K3) merupakan aspek penting dalam profesi berisiko tinggi seperti pemadam kebakaran. Petugas pemadam kebakaran merupakan profesi dengan tingkat risiko tinggi akibat paparan bahaya fisik, kimia, dan psikologis saat menjalankan tugas. Penggunaan Alat Pelindung Diri (APD) menjadi komponen utama dalam upaya perlindungan terhadap cedera dan penyakit akibat kerja. Tujuan: Untuk menganalisis efektivitas penggunaan Alat Pelindung Diri (APD) pada petugas pemadam kebakaran. Metode: Penelitian menggunakan pendekatan literature review dengan sumber data yang diperoleh dari berbagai jurnal yang dipublikasikan dalam lima tahun terakhir (2020-2025). Proses identifikasi literatur dilakukan melalui berbagai platform ilmiah seperti Google Scholar, ResearchGate, ScienceDirect, serta mesin pencari akademik lainnya yang menyediakan akses terhadap jurnal, artikel penelitian, dan publikasi ilmiah relevan. Hasil: Secara keseluruhan, berbagai temuan penelitian tersebut menegaskan bahwa efektivitas penggunaan APD pada petugas pemadam kebakaran tidak hanya ditentukan oleh ketersediaan alat semata. Namun, juga faktor-faktor lain, seperti pelatihan, kondisi peralatan, kesadaran individu, ketersediaan, dan pengawasan dari institusi. Simpulan: Efektivitas penggunaan alat pelindung diri (APD) pada petugas pemadam kebakaran sangat dipengaruhi oleh berbagai faktor yang saling berkaitan.   Kata Kunci: Alat Pelindung Diri (APD); Keselamatan dan Kesehatan Kerja (K3); Petugas Pemadam Kebakaran.